The balance before and after dehydration: an experiment to see the difference - Muhammad Iqbal Purnomo; Patrick John B. Roldan; John Paul A. Cabarles; Janna Marie B. Quinto; Jose Vicente Garcia-Jimenez (Tanjungpura Journal of Coaching Research, 2023)
Background and Study Aim. Balance is the ability to maintain the position of the body when standing, doing activities, also useful equilibrium, posture in order to be able to perform movement activities properly, water is very important for humans which is useful for maintaining cell hemostasis, fluid management interventions that pay attention to intek and output records that te Physical activity is a movement that involves muscles and energy working harder. This study aims to determine the difference in the effect before and after dehydration on body balance.